Les mines d'argent du duché de Lorraine au XVIe siècle Histoire et archéologie du Val de Lièpvre (Haut-Rhin) - Grandemange, Jacques (Documents d'archéologie française, 1991)
The juxtaposition of data from sources as widely differing as account-books and the archaeological remains of a mining System is the keystone of this work devoted to the bistory of the Duke of Lorraine's silver mines in the Lièpvre Valley (Haut-Rhin) between 1512 and 1628. This original approach takes us through a labyrinth of shafts and galleries towards the discovery both of a rational spatial organization, using spécifie building and extraction techniques, and of the economic and political conditions which encouraged its development. This study, at the crossroads of bistory and archaeology, constituiez a precious source of informations both for specialists and for newcomers to the bistory of mining and its techniques.